2011
DOI: 10.1007/s12529-011-9183-4
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Analysis of Fear of Recurrence among African-American Breast Cancer Survivors

Abstract: Background Fear of recurrence (FOR) is a psychological concern that has been studied extensively in cancer survivors but has not been adequately examined in African-American breast cancer survivors. Purpose This exploratory study describes the extent and nature of FOR in African-American breast cancer survivors. FOR is examined in relation to socio-demographic characteristics, treatment-related characteristics, psychological distress, and quality of life (QOL). Methods Participants completed questionnaires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 31 publications
4
48
0
Order By: Relevance
“…Table showed that 55.3% of the patients were farmers and workers, with a larger proportion (56.1%) of whose family income less than or equal to 4000 yuan/month. This result is consistent with other researches . The possible explanation is that low‐income breast cancer patients bear more financial pressure and guilt for family members, and are more concerned that the recurrence of cancer will further aggravate the financial burden on families .…”
Section: Discussionsupporting
confidence: 91%
“…Table showed that 55.3% of the patients were farmers and workers, with a larger proportion (56.1%) of whose family income less than or equal to 4000 yuan/month. This result is consistent with other researches . The possible explanation is that low‐income breast cancer patients bear more financial pressure and guilt for family members, and are more concerned that the recurrence of cancer will further aggravate the financial burden on families .…”
Section: Discussionsupporting
confidence: 91%
“…The incidence of distress scores of 5 or greater (35%) in this cohort was slightly below the national average of 40%–50% reported in the literature for all cancer types (Mitchell et al, 2012; Vitek et al, 2007); however, it is comparable to that of breast cancer survivors (33%) (Hegel et al, 2008). An inverse relationship was found between distress and QOL, with increased levels of distress resulting in poorer QOL scores, which also correlates with findings from the literature (Chachaj et al, 2010; Foster, Wright, Hill, Hopkinson, & Roffe, 2009; Frumovitz et al, 2005; Hodgkinson, Butow, Fuchs, et al, 2007; Hodgkinson, Butow, Hunt, et al, 2007; Leak, Hu, & King, 2008; Menhert & Koch, 2008; Morrow et al, 2014; Ploos van Amstel et al, 2013; Roland, Rodriguez, Patterson, Trivers, 2013; Taylor et al, 2012). Distress scores of 5 or greater were less likely to be associated with increased referrals and multiple adjuvant treatments.…”
Section: Discussionsupporting
confidence: 88%
“…The study team incorporated multiple management techniques for psychosocial support in the innovation cohort to meet the cultural needs of the institution. The interventions included face-to-face or telephone interviews, a tactic supported by the literature (Matulonis et al, 2008; Taylor et al, 2012; Wenzel et al, 2005). This allowed patients to choose consultation preference and increased flexibility for the social workers to optimize their schedules.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that greater time since treatment was associated with greater anxiety deserves further study using a prospective study design given that research in breast cancer has shown that anxiety significantly decreases the farther out patients are from diagnosis [32, 33]. Given that increased symptom burden is associated with more cancer-related worry [33], OC survivors may have been anxious because side effects were not resolving as fast as expected.…”
Section: Discussionmentioning
confidence: 99%